Metabolism of acyl‐lipids in Chlamydomonas reinhardtii. (3rd March 2015) - Li‐Beisson, Yonghua; Beisson, Fred; Riekhof, Wayne
Summary: Microalgae are emerging platforms for production of a suite of compounds targeting several markets, including food, nutraceuticals, green chemicals, and biofuels. Many of these products, such as biodiesel or polyunsaturated fatty acids (PUFAs), derive from lipid metabolism. A general picture of lipid metabolism in microalgae has been deduced from well characterized pathways of fungi and land plants, but recent advances in molecular and genetic analyses of microalgae have uncovered unique features, pointing out the necessity to study lipid metabolism in microalgae themselves. In the past 10 years, in addition to its traditional role as a model for photosynthetic and flagellar motility processes, Chlamydomonas reinhardtii has emerged as a model organism to study lipid metabolism in green microalgae. Here, after summarizing data on total fatty acid composition, distribution of acyl‐lipid classes, and major acyl‐lipid molecular species found in C. reinhardtii, we review the current knowledge on the known or putative steps for fatty acid synthesis, glycerolipid desaturation and assembly, membrane lipid turnover, and oil remobilization. A list of characterized or putative enzymes for the major steps of acyl‐lipid metabolism in C. reinhardtii is included, and subcellular localizations and phenotypes of associated mutants are discussed. Biogenesis and composition of Chlamydomonas lipid droplets and the potential importance of lipolytic processes in increasing cellular oil content are also highlighted. Significance Statement: Increasing societal and economic pressure for finding alternative fuels has pushed microalgal biofuel to the spotlight of both academic and industrial research. The need to improve oil yields begs for more basic research on lipid metabolism in microalgal cells. We summarize here 40 years of research on lipids in the model microalga Chlamydomonas reinhardtii .